From Personal Space to Control Society: The Transformation of Privacy and Surveillance Synergies in the Big Data Era - Gardi, Bayar; Gani, Abdul (Journal of Social Science Studies, 2023)
This literature review examines the profound transformation of privacy and the rise of a convergent surveillance society in the big data era. Through a qualitative thematic synthesis, the study addresses two core questions: the conceptual and structural shifts in the meaning of privacy, and the synergistic power dynamics between corporate and state surveillance. The analysis reveals that privacy has evolved from a right to seclusion into a struggle for contextual integrity and autonomy against predictive profiling and data commodification within surveillance capitalism. Furthermore, the study demonstrates that corporate-state surveillance operates through a deeply integrated ecosystem, forming a hybrid power regime fueled by the surveillance-industrial complex and mutual data dependencies. This convergence fundamentally reshapes power relations, eroding individual autonomy through pervasive chilling effects and restructuring civil liberties by subordinating digital public spaces to commercial and state logics. The result is the crystallization of a control society where social sorting and behavioral modulation become normalized functions of governance. The study concludes that addressing these challenges requires moving beyond individual-centric privacy frameworks towards structural interventions that limit data extraction, regulate concentrated power, and foster technological alternatives designed to uphold democratic sovereignty and collective freedom. The findings underscore the urgent need for integrated analytical perspectives, bold public policy, and a reimagined digital common.